Two developments in Zinnia Subgenera Diplothrix (Compositae: Heliantheae) from central Mexico - Calderon de Rzedowski, Graciela; Rzedowski, Jerzy (Instituto de Ecología, A.C., 1996)
Zinnia acerosa (DC.) A. Gray var. guanajuatensis, from the state of Guanajuato, and Z. zamudiana, from the state of Querétaro, are described as new. The first differs from the typical variety in the prostrate habit, in the wider heads which contain a larger number of flowers, and in the almost completely epappose achenes. The second seems to be related to Z. juniperifolia (DC.) A. Gray, but is remarkably distinct in the prostrate, more or less pulvinate habit, in the sessile or very shortly pedunculate heads, and in the smaller and less intensely colored ligules.